Women with cardiovascular risk after preeclampsia: is there follow-up within the Unified Health System in Brazil? - Maria de Lourdes Costa da Silva; Ana Cristina Araújo de Andrade Galvão; Nilba Lima de Souza; George Dantas de Azevedo; Selma Maria Bezerra Jerônimo; Ana Cristina Pinheiro Fernandes de Araújo (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to identify women with cardiovascular risk, five years after a preeclampsic episode (PE), and identify the follow-up of these women within the Unified Health System (Sistema Único de Saúde - SUS), in the city of Natal/RN. METHODS: a quantitative and exploratory study conducted at the Januário Cicco University Maternity Ward/RN. The sample consisted of 130 women, 65 with a PE episode and 65 who were normotensive. RESULTS: we found statistical significance with regard to body mass index, weight, family history of cardiovascular disease (CVD) and cardiovascular complications when comparing women with previous PE to normotensive women. The groups were unaware of their cardiovascular risk factors and, in addition, they reported difficulties in accessing primary health care (PHC) services. CONCLUSIONS: women with a PE history are at increased risk of developing CVD, unaware of late PE complications, and lacked customized care when compared to normotensive patients.